Dynamic impact testing of cellular solids and lattice structures: Application of two-sided direct impact Hopkinson bar. (February 2021) - Fíla, Tomáš; Koudelka, Petr; Falta, Jan; Zlámal, Petr; Rada, Václav; Adorna, Marcel; Bronder, Stefan; Jiroušek, Ondřej
Highlights: Direct impact Hopkinson bar with two-sided instrumentation used for impact testing. Wave separation method allowed for significant extension of the experiment duration. Wave separation and specimen's response verified with digital image correlation. Experimental setups with both linear elastic and visco-elastic bars used. Metal foams, additively manufactured lattices and hybrid auxetic metamaterials tested. Graphical abstract: Abstract: Direct impact testing with a Hopkinson bar is, nowadays, a very popular experimental technique for investigating the behavior of cellular materials, e.g., lattice metamaterials, at high strain-rates as it overcomes several limitations of the conventional Split Hopkinson Pressure Bar (SHPB). However, standard direct impact Hopkinson bars (DIHB) have only single-sided instrumentation complicating the analysis. In this paper, a DIHB apparatus instrumented with conventional strain-gauges on both bars (a so called Open Hopkinson Pressure Bar - OHPB) is used for dynamic impact experiments of cellular materials. Digital image correlation (DIC) is used as a tool for investigating the displacements and velocities at the faces of the bars. A straight-forward wave separation technique combining the data from the strain-gauges with the DIC is adopted to increase the experiment time window multiple times. The experimental method is successfully tested at impact velocities in a range of 5 − 30 m · s − 1 with both linear elastic and visco-elastic bars of a medium diameter. It is shown that, under certain circumstances, a simple linear elastic model is sufficient for the evaluation of the measurements with the visco-elastic bars, while no additional attenuation and phase-shift corrections are necessary. The applicability of the experimental method is demonstrated on various experiments with conventional metal foams, hybrid foams, and additively manufactured auxetic lattices subjected to dynamic compression.